Research methods in education : - Wiersma, William (Pearson/Allyn and Bacon, 2009)
This book/CD-ROM text for graduate students in education explains the research process, with emphasis on the formulation of a research question, referencing current literature in the field, using appropriate qualitative and quantitative research designs, and writing and evaluating research reports. Measurement, sampling, and statistics are presented as essential research tools. An appendix addresses ethical and legal considerations. Two more appendices list selected answers to chapter exercises, and offer reference statistical tables. A glossary is also included. For this 9th edition, chapters have been reorganized into three sections on the overall research process, research designs, and research tools. New examples have been added to capture students' interest, and new chapter exercises are included. Statistics chapters have been updated with new data sets. The CD-ROM contains data in Excel and SPSS formats, for use with statistical exercises.